2012
DOI: 10.1590/s1516-31802012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Mentors also need support: a study on their difficulties and resources in medical schools

Abstract: Like in other mentoring programs, many difficulties perceived by mentors seem to be derived from the context of medical education itself. However, unlike in other experiences, FMUSP mentors do not feel that there is lack of support for their role, since this is regularly provided in the structure and dynamics of the program. The "difficulty in perceiving difficulties", presented by some mentors, demands further investigation for better and greater understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 26 publications
(44 reference statements)
1
24
0
9
Order By: Relevance
“…25 In addition to a mentor's time, programmatic time also needs to be devoted to organizing the program, training mentors and protégés, and identifying extramural funding to support the mentorship program. 26,27 Funding for the mentoring program could be used to hire support staff members; engage external trainers, consultants, and mentors; and provide grant release time to mentors. Such support has been shown to increase the amount of extramural funding generated by the protégés, and in the long run, may contribute to faculty retention.…”
Section: Resources Needed For Mentoring Programsmentioning
confidence: 99%
“…25 In addition to a mentor's time, programmatic time also needs to be devoted to organizing the program, training mentors and protégés, and identifying extramural funding to support the mentorship program. 26,27 Funding for the mentoring program could be used to hire support staff members; engage external trainers, consultants, and mentors; and provide grant release time to mentors. Such support has been shown to increase the amount of extramural funding generated by the protégés, and in the long run, may contribute to faculty retention.…”
Section: Resources Needed For Mentoring Programsmentioning
confidence: 99%
“…21,22 This lack is surprising given the evidenced widespread benefits, 15,21 although it could be argued that there has been uneven support and guidance for potential mentors to enable them to adopt such roles. 23 Mentors provide strong role modelling for careers and can have a significant impact on specialty choice. 21,24 In a study including over 9000 medical students, mentors and role models were identified as the most or second-most influential factor in determining specialty selection; for 'controllable lifestyle' specialties, of which psychiatry was included, their influence was exceeded only by 'lifestyle factors'.…”
Section: Discussionmentioning
confidence: 99%
“…La investigación en torno a las cuestiones críticas en la conformación de programas de tutoría y mentoría deben ser de igual forma señaladas, toda vez que tales registros influyen en el perfeccionamiento de esas herramientas pedagógicas. En este sentido, el análisis de las publicaciones nacionales indica que los tutores y mentores en las universidades brasileñas presentan dificultades en su formación, entre las que se encuentran: dudas en cuanto a las funciones y acciones que pueden desempeñar y el limitado tiempo que poseen para desarrollar la relación entre tutor y estudiante (Gonçalves, 2011;Gonçalves & Bellodi, 2012b;Gonçalves & Bellodi, 2012a), así como la incomprensión en torno a sus roles como mentor (Silva, 2007).…”
Section: Discussionunclassified
“…Los estudios centrados en las valoraciones sobre las características inherentes a un tutor o mentor ideal (Monte, 2011;Urban, 2011) corroboran lo señalado por la literatura respecto a la necesidad de la preparación metodológica (Aguilar et al, 2012), y de la flexibilidad y la empatía (Simão et al, 2008;Flores et al, 2011). Entre tanto, algunos tutores entrevistados manifestaron su desinterés sobre tales procesos tranformadores de la enseñanza (Gonçalves, 2011;Gonçalves & Bellodi, 2012b;Gonçalves & Bellodi, 2012a), pues son partidarios de la praxis pedagógica tradicional (Pinheiro, 2009). Esto es reflejo, por un lado, de la poca disponibilidad de docentes para la práctica de la mentoría; por otro, de la falta de preparación y sensibilización de los profesores para actuar como mentores/tutores.…”
Section: Discussionunclassified